Nesting ecology of Lesser Grey and Woodchat Shrikes in Apulia, southern Italy (Avocetta, 2020)
True shrikes (family Laniidae, genus Lanius) are birds highly associated with open and farmed landscapes and have suffered significant declines all over the world, especially due to increasingly intense agriculture and climatic fluctuations. In Italy, three species breed: Red-backed Shrike Lanius collurio, Lesser Grey Shrike Lanius minor and Woodchat Shrike Lanius senator. All three are threatened and considered Vulnerable (the first two species) or Endangered (the latter species) in Italy. The purpose of this study was to provide new insights on the nesting ecology of Lesser Grey and Woodchat Shrikes in Italy by territory mapping in six sampling areas in Apulia in 2009-2013. I also collected data on nest location and breeding success. I mapped 93 territories of Lesser Grey Shrike (for 127 breeding attempts) and 84 territories of Woodchat Shrike (for 107 breeding attempts) and noted a decline in shrike numbers over the five years. Most territories of Lesser Grey Shrikes were used for one nesting attempt (71.0%) and the remainder used twice, showing a clear site fidelity. Similarly for the Woodchat Shrike, more than 20% of territories were used for two nesting attempts. Both species formed solitary pairs, but 5% of Lesser Grey Shrike formed two-pair clusters and I found only a single two-pair cluster of Woodchat Shrikes. Lesser Grey Shrikes nested in isolated trees (mainly oaks, elms, almond, and olive trees), building a nest at 4.2 m above the ground, partially hidden and placed in a distal position respect the tree trunk. The first record of Macedonian Oak and Olive being used for nest support was obtained. I found only three nests of the Woodchat Shrike. Fledged broods of Lesser Grey Shrike composed on average 2.3 juveniles; for the Woodchat Shrike this value is 1.9 juveniles.
Keywords: Lanius; shrikes; steppe birds; farmland birds; Mediterranean Basin